STRATEGI KOMUNIKASI PT. BANK NEGARA INDONESIA (PERSERO) Tbk DALAM ACQUISITION AND EXISTING POTENTIAL NASABAH EMERALD DI Kcp. MARTAPURA - Rizki Fatmala; Bianca Virgiana; Septiana Wulandari (Jurnal Komunikasi dan Budaya, 2020)
Competition between banks in attracting customers makes PT Bank Negara Indonesia must have a communication strategy to be able to attract and retain customers.The theory used in this research is the strategy selection model theory that discusses how communication actors choose message strategies to achieve their objectives. Achieving fulfillment from others is one of the goals of communicationIn this study, researchers used a qualitative descriptive study using in-depth interviews with informants to obtain valid data.The results of this study explain the decline in Emerald customers at PT. Bank Negara Indonesia (Persero) Tbk in KCP. Martapura is due to the decline in fulfillment of Asset Under Management (AUM) customers from the Emerald target which, if decreased, is subject to a fine of two hundred and fifty thousand a month to still be an Emerald customer, but due to customer needs and unable to meet its AUM targets, many choose to down grade than paying a fine.The conclusion from this study of the 9 theories chosen to see communication strategies there are two theories that are not fulfilled, namely promises and leads to moral obligations, fulfillment of the agreement is not carried out properly because there are still customers who do not maintain the Emerald balance target and are required to pay fines for continue to receive Emerald services, Leading to moral obligations, customers do not meet the obligations of the Emerald balance target and object to paying fines and choosing a downgrade from Emerald customers